The Lived Experiences of Male Early Childhood Educators: Insights from Qualitative Interviews - Maria Fatima Perales-Dolendo (Research Synergy Foundation, 2025)
Male educators in early childhood education represent a small but vital demographic. However, their experiences and challenges have mainly been underexplored due to persistent gender stereotypes and the historically female-dominated nature of the field. This study aimed to address this gap by exploring the lived experiences of male early childhood educators, shedding light on their professional challenges, contributions, and perspectives. Employing a phenomenological research design, the study utilized Colaizzi’s method to analyze data from in-depth semi-structured interviews with ten (10) purposefully selected male educators, each with a minimum of two years of teaching experience. The findings revealed three primary themes. First, male educators demonstrated their resilience and adaptability by using a variety of coping mechanisms to navigate professional and societal challenges, including gender biases and parental skepticism. Second, despite these challenges, they conveyed a deep sense of professional fulfillment from their work, emphasizing their passion for fostering young children’s holistic development and their commitment to reshaping perceptions of male educators in early childhood settings. Lastly, the results highlighted the increasing interest in male educators as essential father-like figures and positive male role models, reinforcing the need for greater gender inclusivity in early childhood education. The results showed that male educators are as capable of providing excellent learning opportunities and experiences as their female counterparts. Their distinct viewpoints and methods helped create a more varied and stimulating learning environment. This study challenges traditional gender norms and advocates for a more inclusive and equitable early childhood education workforce.